Heritage-Led Urban Regeneration in Rome: Recontextualising the Campo Trincerato through Network Strategies - Perrone, Francesca; Imbesi, Paola Nicoletta; Ricci, Laura (Journal of Contemporary Urban Affairs, 2025)
Contemporary peri-urban landscapes face fragmentation, marginalisation, and the neglect of widespread cultural heritage. This article explores heritage-led regeneration as a strategic framework to revitalise marginal areas by focusing on the Campo Trincerato in Rome, a system of fifteen forts and three batteries constructed between 1877 and 1891. Despite being largely abandoned, these fortifications remain structurally intact and spatially coherent, offering opportunities for reconceptualisation as infrastructural nodes within broader urban and territorial networks. The study adopts a multi-scalar methodological approach, combining architectural analysis of typological and structural features with contextual investigation of accessibility, ownership, and planning frameworks. Results reveal that while the Campo Trincerato maintains its systemic coherence, institutional fragmentation and limited reuse represent major barriers to regeneration. Nevertheless, its configuration as a defensive ring highlights potential to establish cultural polarities, ecological connections, and community-driven functions in Rome’s suburban areas. The findings underscore the significance of integrating cultural heritage into contemporary regeneration strategies, transforming neglected military infrastructure into catalysts for urban identity, social cohesion, and sustainable development.